Effect of mobile phones as a magnetic field on the microhardness of human teeth - KARGÜL, BETÜL; YILMAZ, MÜESSER AHU (My University, 2016)
To investigate the effect of radiofrequency (RF) radiation emitted from 900 MHz mobile phones on the enamel and cementum microhardness of human teeth. Methods A number of sources emit electromagnetic fields especially radiofrequencies are growing rapidly in the world we live today. A total of 32 freshly extracted human premolar teeth were prepared for the study group. A generator which produces 900 MHz radiofrequency radiation was used in this study to represent exposure of global systems for mobile communication (GSM). Teeth were exposed to the radiation for 2 h per day (7 days a week) for 12 months. Digital micro-Vickers hardness tester (Wilson Wolpert Europe BV, 401 MVD, Netherlands) fitted with a Vickers diamond and a 200 N load was used to make indentations in the enamel and cementum surfaces. Data were analysed using SPSS 16.0 software. Paired sample t test was used (p\0.05). Results The mean baseline microhardness in enamel (165.82 ± 56.63) was found to be lower than after exposure (163.80 ± 24.53). However, difference between baseline and after exposure were not found to be statistically significant (p = 0.855). The mean value of baseline cementum surface was 41.15 ± 13.81 and after radiation was 26.16 ± 8.13. There were statistically significant differences between pre- and post-radiation in cementum (p = 0.000). Conclusions Despite this result of this study, it can be considered that long term exposure of 900 MHz radiofrequencies emitted from mobile phones may decrease the microhardness of teeth.